Evaluation of the sports inheritance of she ethnic intangible cultural heritage: A fuzzy comprehensive assessment approach - Guo, Yonghong; Karim, Zulakbal Abd; Wang, Feng; Wang, Yinan (Edelweiss Applied Science and Technology, 2025)
This study evaluates the inheritance of She ethnic sports intangible cultural heritage using a fuzzy comprehensive assessment approach to identify key preservation factors and their interrelationships. The research employs a mixed-methods design combining Analytic Hierarchy Process (AHP) weighting, regression analysis, and fuzzy logic evaluation to assess five primary dimensions: inheritor factors, activity effectiveness, educational investment, facility conditions, and social acceptance. Findings reveal a balanced but suboptimal preservation status, with educational resources emerging as the strongest predictor and social acceptance as the most challenging dimension. Secondary analysis highlights critical sub-factors, including inheritor participation and resource utilization efficiency, while interaction effects demonstrate significant synergies between education and activity implementation. The results align with prior cultural heritage research while providing novel quantitative insights specific to She ethnic sports, confirming that successful preservation requires integrated strategies addressing all dimensions, with particular emphasis on education-activity linkages. The study contributes methodologically by demonstrating fuzzy logic's effectiveness in handling cultural heritage complexity and offers practical implications for policymakers: prioritizing participatory educational programs, optimizing resource use over mere funding increases, and fostering community engagement to convert awareness into active preservation. These findings advance both theoretical understanding and practical approaches to safeguarding intangible cultural heritage in minority communities.